WEBVTT
00:00:01.610 --> 00:00:09.160
Add seven 𝑎 plus six 𝑏 squared to five 𝑐 cubed plus 𝑏 squared minus five 𝑎.
00:00:10.840 --> 00:00:21.340
Adding the two expressions initially gives us seven 𝑎 plus six 𝑏 squared plus five 𝑐 cubed plus 𝑏 squared minus five 𝑎.
00:00:22.730 --> 00:00:28.390
We can group or simplify the two 𝑎 terms and the two 𝑏 squared terms.
00:00:29.960 --> 00:00:36.610
Grouping the two 𝑎 terms gives us two 𝑎 as seven 𝑎 minus five 𝑎 is equal to two 𝑎.
00:00:38.360 --> 00:00:46.880
Grouping the 𝑏 squared terms gives us seven 𝑏 squared as six 𝑏 squared plus 𝑏 squared is equal to seven 𝑏 squared.
00:00:48.420 --> 00:00:50.540
There is only one 𝑐 cubed term.
00:00:50.750 --> 00:00:53.270
So we cannot simplify or group this.
00:00:54.920 --> 00:01:08.000
This means that seven 𝑎 plus six 𝑏 squared plus five 𝑐 cubed plus 𝑏 squared minus five 𝑎 is equal to two 𝑎 plus seven 𝑏 squared plus five 𝑐 cubed.